2018
DOI: 10.1080/10503307.2018.1453621
|View full text |Cite
|
Sign up to set email alerts
|

“It was like having half of the patient in therapy”: Therapists of nonimproved patients looking back on their work

Abstract: This split picture was interpreted as a sign of a pseudo-process emerging when the therapist one-sidedly allied herself with the patient's capable and seemingly well-functioning parts. The therapists' experiences could be compared to the nonimproved patients' "spinning one's wheels" in therapy. The therapists seem not to have succeeded in adjusting their technique to their patients' core problems, despite attempts to meta-communicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It is possible that people undertaking a new therapy commit themselves to being open, honest, and vulnerable in ways that enable their therapists to do good work with them (cf., McKenna and Todd, 1997). Accordingly, in our previous studies, the proportion of patients with previous psychotherapy experience was higher in the successful cases than in cases of non-improvement (Werbart et al., 2018, 2019). Furthermore, in the successful cases, the patients mentioned supportive life circumstances and getting support in close relationships (Palmstierna and Werbart, 2013), whereas non-improved patients reported both helpful life conditions and negative impacts of life events (Werbart et al., 2015).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It is possible that people undertaking a new therapy commit themselves to being open, honest, and vulnerable in ways that enable their therapists to do good work with them (cf., McKenna and Todd, 1997). Accordingly, in our previous studies, the proportion of patients with previous psychotherapy experience was higher in the successful cases than in cases of non-improvement (Werbart et al., 2018, 2019). Furthermore, in the successful cases, the patients mentioned supportive life circumstances and getting support in close relationships (Palmstierna and Werbart, 2013), whereas non-improved patients reported both helpful life conditions and negative impacts of life events (Werbart et al., 2015).…”
Section: Discussionmentioning
confidence: 70%
“…They seemed to underestimate their patients’ problems and their unprocessed positive countertransference contributed to the view of being on the right track. At termination, they concluded that the patients needed more time in therapy, attributing the limited progress to the patients’ resistance rather than their own limitations (Werbart et al., 2018). On the other hand, in successful cases, the therapists described active, relational work that included paying attention to incongruities in the patient’s self-presentation and being mindful of the patient’s avoidant behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, previous studies from YAPP explored, among other things, the patients' (Lilliengren & Werbart, 2005) and the therapists' (Lilliengren & Werbart, 2010) view of therapeutic action, dissatisfied patients (von Below & Werbart, 2012), nonimproved patients (Werbart et al, 2015), successful cases (Palmstierna & Werbart, 2013), therapists' view of successful and less successful cases, (Werbart et al, 2018), and within-therapist differences between successful and less successful psychotherapies . From these studies it was obvious that dissatisfaction, as expressed by patients, and non-improvement, as measured by symptom reduction in the YAPP sample, did not always coincide.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at unsuccessful treatments more closely, it becomes evident that both therapist and patient evaluated the therapeutic relationship to be distant at the beginning of therapy. Based on this reserved relationship, the therapists were not capable to adapt the treatment plan accordingly (Werbart et al, 2018). For successful treatments, both therapist and patient felt a strong connection: they felt sympathetic, thoughtful and liked each other (Werbart, Missios, et al, 2019).…”
Section: Future Researchmentioning
confidence: 99%